Socioeconomic indicators and economic investments influence oral cancer mortality in Latin America - Aldelany Ramalho Freire; Deborah Ellen Wanderley Gomes Freire; Elza Cristina Farias de Araújo; Fernanda Campos de Almeida Carrer; Gilberto Alfredo PuccaJúnior; Simone Alves de Sousa; Edson Hilan Gomes de Lucena; Yuri Wanderley Cavalcanti (BMC, 2021)
Abstract Background It is necessary to recognize the influence of socioeconomic factors on oral cancer indicators in Latin American countries. This study aimed to analyze the influence of socioeconomic indicators and economical investments on oral cancer mortality rates in Latin American countries. Methods This cross-sectional study considered the age-standardized mortality rate (ASR) of oral cancer within the period 2000-2015. The oral cancer mortality rate (for both sexes and age groups 40-59 and 60 years old or more), socioeconomic aspects (Gini Inequality Index, unemployment rate and Gross Domestic Product (GDP) per capita) and investments in different sectors (%GDP invested in health per capita and by the government, %GDP invested in education by the government and %GDP invested in research and development) were considered. Tweedie multivariate regression was used to estimate the effect of independent variables on the mortality rate of oral cancer, considering p < 0.05. Results This study showed that being male and aged 60 or over (PR = 14.7) was associated with higher mortality rate for oral cancer. In addition, greater inequality (PR = 1.05), higher health expenditure per capita (PR =1.09) and greater investment in research and development (PR = 1.81) were associated with a higher mortality rate from oral cancer. Conclusion Socioeconomic factors and economical investments influence the mortality rate of oral cancer in Latin American countries. This emphasizes oral cancer is a socioeconomic-mediated disease.